Distances and other measures of nearness in a set of pairs of black-and-white digital images - P. G. Parfenov; I. A. Kapliy; O. S. Kulikov (Моделирование и анализ информационных систем, 2007)
In the paper is formulated series of functions in a set of pairs of black-and-white digital images. Series of functions are either distance or distance analogue. This functions allows, on the one hand, to solve a problem of discerning images, and on the other hand, to measure similarity. Applications of this approach to textures are examined.